The Role Of Fandom Culture In K-Pop Merchandise Purchase Decisions Among Indonesian Fans - Niken Kiranaputri; Novika Candra Astuti (International Journal of Management and Business Economics, 2026)
The research initially begins with the very high intensity K-pop fandom culture that facilitates digital involvement in Indonesia, although it is not accompanied by the buying of official merchandise in all cases. Therefore, the present research seeks to study fandom culture by investigating influence which influence the purchasing decision of Indonesian fans purchasing K-pop merchandise and findings which motivate and prevent purchasing. This study uses a quantitative methodology through an online survey among Indonesia's K-pop fans, and it is subsequently statistically evaluated in terms of the relationships between variables. The investigation demonstrates that culture of fandom and digital engagement have an impact on purchases but a conversion from digital fandom to purchase behaviour is also a function of value, purchasing power and perceived benefit of the product. We can conclude from these observations that culture of fandom offers more than just emotional support; it also influences consumption behavior, which has a strategic implication for K-pop agencies that can formulate more effective promotional campaigns with product sale potential.